Efek Mekanisme Good Corporate Governance dan Kinerja Keuangan terhadap Nilai Perusahaan - Iin Ariska; Mohamad Nur Utomo (Universitas Serang Raya, 2021)
This study aims to examine the effects of institutional ownership, independent board of commissioners, profitability and liquidity on firm value. Goods and consumer manufacturing companies listed on the Indonesia Stock Exchange were sampled in this study with the period 2015 to 2019. Data analysis used statistical methods. The results showed that Institutional Ownership and Profitability had a positive and significant effect on firm value. Meanwhile, the independent board of commissioners has a negative and insignificant effect on firm value, liquidity has a positive and insignificant effect. This study implies that increased monitoring of institutional shareholders and increased performance is an effective way to increase firm value. In addition, the company must continue to improve the supervisory role of the independent board of commissioners and maintain the level of liquidity in order to have a long-term advantage.